PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP FINANCIAL RESTATEMENT (Studi Empiris Terhadap Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2016-2017) - Aulia Putri Ananda; Andreas Andreas; Volta Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of audit committee characteristics on financial restatements. Audit committee characteristics used in this studied are audit committee meeting, audit committee size, audit committee independence, and audit committee expertise. The population in this study is all companies listed on Indonesia Stock Exchange (IDX) in 2016-2017. Research sample is determined using a purposive sampling method. The data in this research is obtained by annual reports of 136 companies that have restated their financial restatements multiplied 2, resulting in a total of 272 samples. This study uses the Logistic Regression as a method of analysis. The results prove that audit committee meeting has an positive effect on financial restatements and audit committee independence has an negative effect. Meanwhile, audit committee size and audit committee competency has not effect on financial restatements.Keywords : Audit Committee Characterisitc, Corporate Governance, Financial Restatement